Search by Image Through the Internet: An Additional Method to Find Information - Nieuwenhuysen, Paul (2015)
Offers an overview of an ongoing assessment of search by image through the Internet. This is a relatively new method for information retrieval, in which a query does not consist of text but of an image file. Various tests have been performed. The results show that search by image is evolving to a powerful, additional method to meet information needs that are difficult to handle with other, more classical methods. Various types of applications are presented.